Determining the Relationship Between the Frequency of Urinary Incontinence, Depression, Anxiety and Stress in Menopausal Women - Arzu Abiç; Sinem Dağ Canatan; Ahu Aksoy Can (Mediterranean Nursing and Midwifery, 2023)

(untitled)
Objective:Though urinary incontinence (UI) is not a life-threatening health problem, it may have significant physical and psychological effects on women’s social and family life. Most women delay seeking help since they are embarrassed or do not consider UI a health problem, causing a gradual increase in the symptoms of UI. This study aims to determine the relationship between the frequency of UI, depression, anxiety, stress and quality of life in menopause women.Method:The sample of this descriptive study comprised 112 participants from Northern Cyprus between October and December 2022. Personal information form, urogenital distress inventory (UDI-6), incontinence impact questionnaire (IIQ-7) and depression, anxiety, stress scale-21 (DASS-21) were used for data collection. The non-parametric Mann-Whitney U test was used for two-group comparison. Spearman’s correlation coefficient was used to determine the relationship between two continuous variables. Number, percentage, mean and standard deviation were used as descriptive statistics. Statistical significance was set at p<0.05.Results:The mean scores obtained by the participants with UI from all scales and their subscales were significantly higher than the participants without UI (p<0.05). There was a positive, moderate and statistically significant relationship between the UDI-6, IIQ-7 and the depression, anxiety and stress subscales of DASS-21 (r=0.634, p<0.001; r=0.449, p<0.001; r=0.609, p<0.001; r=0.449, p<0.001, r=0.492 p<0.001, respectively). In addition, it was also found a positive, moderate and statistically significant relationship between the IIQ-7 and the depression, anxiety and stress subscales of DASS-21 (r=0.517, p<0.001; r=0.591, p<0.001; r=0.619, p<0.001, respectively).Conclusion:This study found that a higher frequency of UI in menopausal women reduced the quality of life and increased the levels of depression, anxiety and stress.